Alternative strategies of recurrent selection for seed yield of soybean - Guimarães, Elcio Perpétuo; Fehr, WR (1989)
Recurrent selection programs can be manipulated by varying either the extensiveness of testing used to identify superior lines or the number of intermating generations conducted among the superior lines between cycles of selection. The research was conducted to compare the performance of soybean (Glycine max (L.) Merr.) lines derived from populations developed by recurrent selection for seed yield using a factorial arrangement that combined one or two stages of replicated yield testing to identify superior lines with one or three generations of intermating among the selected lines. The base population AP6, which was used for this evaluation of alternative strategies of recurrent selection, was derived from 40 high-yielding strains of Maturity Groups 0 to IV. For this study, the 40 original parents of AP6 and the lines used as the parents for the most advanced cycle of selections for each of the strategies were evaluated in four Iowa environments. The number of cycles of selection completed for the strategies under evaluation varied from two to five. Strategies with two stages of replicated yield testing to select superior lines resulted in a larger number of high-yielding lines than when only one stage of testing was conducted. A larger number of high-yielding lines was obtained from strategies with one generation of intermating than when three generations were used. With the procedures used for the one-stage and two-stage tests in this study, the results indicated that an appropriate strategy for recurrent selection of seed yield in soybean would involve two stages of replicated yield testing to identify superior lines and one generation of intermating among the selected lines to form a new population.